Perbandingan Diagram Kontrol Demerit dan Fuzzy u: Studi Kasus : Kecacatan Produk Kayu Lapis (Plywood) di PT. Segara Timber Mangkujenang, Samarinda Provinsi Kalimantan Timur Tahun 2019 - Septilasse, Rebeka Norcaline; Goejantoro, Rito; Wahyuningsih, Sri (EKSPONENSIAL, 2020)
Control chart is a graph that provides a picture of a running process whether under controlled conditions or not. Demerit control chart and fuzzy u control chart are very suitable for production quality control. This study was applied to the data of defects of plywood products at pt. segara timber, samarinda, east Kalimantan in 2019. The purpose of this study is to get the results of a comparison of the decision of Demerit control chart and fuzzy u control chart. The results of this study shows the demerit control chart is more thorough than the fuzzy u control chart due to the demerit control chart found 12 out of control observations and the fuzzy u control chart only found 1 out of control observations.